2005
DOI: 10.1007/s00268-004-7635-6
|View full text |Cite
|
Sign up to set email alerts
|

Mammotome: Less Invasive than ABBI with Similar Accuracy for Early Breast Cancer Detection

Abstract: Abstract. We performed a prospective analysis of two consecutive biopsy cohorts investigated by the same team to compare the Mammotome system with the ABBI procedure. From April 1997 to August 2003 a series of 413 nonpalpable mammographic lesions in 387 women (median age 56 years, range 30-84 years) were stereotactically biopsied in the University Hospital of Basel, Switzerland. Until October 1999 the ABBI system was applied exclusively, it was subsequently superseded by the Mammotome device in our clinic. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…While the ABBI procedure tends to be less invasive than the traditional open surgical biopsy, this technique has not gained widespread acceptance. It uses a probe with a rotating circular knife and thin heated electrical wire to remove a large cylinder of abnormal tissue 47 . In some centres, the biopsy is guided by an MRI, which locates the tumours, plots its co-ordinates, and aims the stereotactic biopsy device into the tumour.…”
Section: The Abbi Methods (Abbi Also Known As Large Core Biopsy Is a Bmentioning
confidence: 99%
“…While the ABBI procedure tends to be less invasive than the traditional open surgical biopsy, this technique has not gained widespread acceptance. It uses a probe with a rotating circular knife and thin heated electrical wire to remove a large cylinder of abnormal tissue 47 . In some centres, the biopsy is guided by an MRI, which locates the tumours, plots its co-ordinates, and aims the stereotactic biopsy device into the tumour.…”
Section: The Abbi Methods (Abbi Also Known As Large Core Biopsy Is a Bmentioning
confidence: 99%
“…• the pooled data suggested that vacuum-assisted breast biopsy with ultrasonography or X-ray mammography could be promising for diagnosis and treatment of breast disease • the results from the 36 articles with 20 868 cases showed high technical success and low complication risks including haematoma, bleeding, skin ecchymosis, pain, vasovagal reflex, and infection • the combination of VABB with US or mammography could be a promising candidate of the standard biopsy methods for detecting nonpalpable lesions controlled trial (RCT) (74 cases), 40 and 4 non-randomised controlled trials (NRCTs) (574 cases), [41][42][43][44] describing a total of 20 868 patients (mean age, 36-56 years), derived from China (7), United States (6), Italy (5), Germany (5), Korea (2), Japan (2), Spain (1), Poland (1), France (1), United Arab…”
Section: Key Messagesmentioning
confidence: 99%
“…Particularly, it is unique for nonpalpable breast lesions and mammography‐detected microcalcifications (2–6). Second, compared with the classic biopsy core, MMT probe could obtain much larger volume sample, resulting in high accuracy and specificity in pathologic diagnosis (1–11). Finally, the MMT procedure is accomplished by single minimal invasion, resulting in minimal risk of needle tract seeding of breast cancer (12).…”
mentioning
confidence: 99%
“…Finally, the MMT procedure is accomplished by single minimal invasion, resulting in minimal risk of needle tract seeding of breast cancer (12). Accordingly, MMT system other than any of automated core needle, the advanced breast biopsy instrument system, fine needle aspiration biopsy and diagnostic surgery, is still the best for breast biopsy (7,9,10,13–15).…”
mentioning
confidence: 99%